The Arts Interview. Des Walsh : Rebellious Light - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Division of Educational Technology, 1984)
An interview by host Fred Hollingshurst with Des Walsh, a Newfoundland poet. Walsh reads his poem "Rebellious Light", then discusses the development of his personal poetic style; how it has been affected by living in Newfoundland. Includes a poetry video with music by Justin Hall, Wallace Hammond, Craig Squires, Des Walsh and Don Wherry.